Basambur Healing Rituals on Etnomedicine of Dayak Paramasan Meratus: Collective Mindset Effect on Perception Response - Muhammad Anshari (CNJ: Caring Nursing Journal, 2018)
The situational meaning of the disease can cause distress, the meaning is generated from the perception process. Perception can be affected by the mindset. To explain the effect of the collective mindset (belief and value) on the perceptual response. The research was conducted in the Dayak Paramasan community of Banjar District. pre-experimental one group pre-post test. Subjects were 12 people with acute respiratory diseases. The research instrument used questionnaire. Data analysis techniques using different test paired sample t test. There is difference of pre-post belief and value variable (sig. 0,000 <0,05). There is difference of pre-post value of perception variable (sig. 0,000 <0,05). The relationship of change of mindset (belief and value) to change of perception variable showed strong and significant relationship (p <0,05); value (r = 0.892), belief (r = 0.908). Ritual basambur can strengthen the collective mindset (belief and value). The dominant mindset will induce perception to establish a positive quality of perception stress. Through the path of HPA axis the body provides a positive stress response quality as well as decreasing the status of distress to support healing.